Sawikaan 2004 mga salita ng taon - Zafra, Galileo S.; Baquiran, Romulo P. (Diliman, Quezon City University of the Philippines Press, 2005)
Compilation of new Tagalog words widely used in 2004 in the Philippines.
In Tagalog.
Keywords: Filipino language -- New words